A study on effective mechanisms for secret sharing in Distributed Blockchain Systems - P Sri Vyshnavi, Chintham Nithisha, A Supriya (Mathematical Statistician and Engineering Applications, 2023)
The primary goal of the paper is to study the mechanisms incorporated for secret sharing by maintaining the costs incurred in distributed blockchain systems. A conventional ledger is maintained in one location with just one copy and the data is validated by a central authority. But the data can be modified and in case of any misfortune happens, the data is not recoverable. In distributed ledger, the copy of ledger is shared amongst multiple nodes. The data is immutable and validated by the participants in the network. If a data segment is lost, then the actual data is unrecoverable. Blockchain is a type of distributed ledger technology, where the transactional data is stored in the form of chain of block. Each block generates a hash code (Unique for each block) that can be used for proof of validation. Each node holds an entire ledger copy, which incurs hefty storage costs. Distributed Storage Blockchain includes private key encryption scheme, information dispersal algorithm(IDA) scheme, and shamir’s secret sharing scheme as well. This reduces storage cost but incurs high communication cost and also it requires additional storage to store hash code & distribute sections of it to each node. A unique DSB approach with Local Secret Sharing scheme has been put forth, to lower the storage and recovery communication costs. This paper studies about the different techniques that are used in distributed blockchain systems for efficient secret sharing. Also, increasing system security is vital for preparing for any future scenarios. As steganography (using image processing) does not require scrambled data or secret keys to conceal the sensitive information, the idea is to integrate the DSB technique with LSS and steganography.